A process and device for co-production of petroleum-based impregnating pitch and coating pitch

CN117701291BActive Publication Date: 2026-10-23CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311555550.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2026-10-23
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

由此可知,目前包覆沥青的制备工艺主要采用真空压力下交联或缩合反应,导致反应过程中大量轻组分被脱除,虽然保证了产品较高结焦值,但产品收率却大幅降低,仅为20-30%,而原料的70-80%则以液体生成油的形式排出,导致原料利用率极为低下

Benefits of technology

[0024]本发明提出了一种石油基浸渍沥青与包覆沥青联产工艺与装置,克服了目前浸渍沥青、包覆沥青间歇操作导致产能低、产品性能不稳定,尤其是原料预处理、真空反应条件所导致的产品收率低等问题。通过对石油基原料进行简单的闪蒸处理实现轻重组分切割,重组分采用超重力脱挥工艺制备超高功率石墨电极用浸渍沥青,轻组分采用超重力氧化交联、超重力脱挥组合工艺制备锂电负极用包覆沥青产品,既实现了产品收率的大幅提升,又实现原料各组分多级有效利用,大幅提升附加值。其中浸渍沥青满足以下指标:软化点为80-120℃,喹啉不溶物<0.5%,甲苯不溶物>10%,结焦值>47%;包覆沥青满足以下指标:软化点为180-280℃,喹啉不溶物<1%,结焦值为55-75%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117701291B_ABST
    Figure CN117701291B_ABST
Patent Text Reader

Abstract

The application discloses a petroleum-based impregnated asphalt and coated asphalt co-production process and device, and belongs to the technical field of petroleum-based impregnated asphalt and coated asphalt production.The petroleum-based impregnated asphalt and coated asphalt co-production process comprises the following steps: fractionating petroleum-based raw materials to obtain raw material light components and raw material heavy components; treating the raw material heavy components by using an ultra-gravity devolatilization treatment to obtain impregnated asphalt products and impregnated asphalt light component removal; mixing the raw material light components and the impregnated asphalt light component removal together with coated asphalt products, and then performing an ultra-gravity oxidative crosslinking reaction; and continuously circulating a first part of the generated oxidation asphalt into the mixture, and treating a second part of the generated oxidation asphalt by using an ultra-gravity devolatilization treatment to obtain coated asphalt products.The petroleum-based impregnated asphalt and coated asphalt co-production process and device can improve the product yield of petroleum-based raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power battery electrode materials technology, specifically to a process and apparatus for the co-production of petroleum-based impregnated bitumen and coated bitumen. Background Technology

[0002] Graphite materials are widely used as anode materials in lithium-ion batteries due to their high specific capacity, long cycle life, and low lithium insertion / extraction plateau voltage. However, the poor compatibility between graphite electrodes and organic electrolytes leads to the formation of excessive SEI films on the anode surface. This not only consumes lithium ions in the electrolyte but also significantly increases interfacial impedance, causing electrochemical kinetic obstacles and even dissociation and peeling of the graphite layer. Consequently, the cycle performance and energy density of lithium-ion batteries are greatly reduced, and their lifespan is significantly shortened. To avoid this problem, researchers have conducted extensive studies on graphite modification and treatment. Among these, graphite surface coating has attracted widespread attention due to its simple and effective process. This method mainly involves coating the graphite surface with a layer of amorphous carbon. Due to the good compatibility of amorphous carbon with organic solvents, it retains the low voltage plateau and high capacity of the graphite electrode while avoiding direct contact between the graphite electrode and the electrolyte, reducing electrochemical impedance, and further improving the cycle performance and rate performance of lithium-ion batteries.

[0003] Currently, there are numerous domestic technologies for preparing coated asphalt. Chinese patent CN107163971A discloses a continuous production method for asphalt-based carbon material raw materials. This process employs preheating filtration, vacuum distillation, vacuum thermal condensation, and scraped-film evaporation to prepare high-softening-point coated asphalt for lithium-ion battery coating materials with a softening point greater than 250℃. CN112592734A discloses a continuous production method for lithium-ion battery anode coating materials, which uses a combination of raw material preheating, distillation cutting, vacuum short-path evaporation, and high-temperature filtration to prepare asphalt products with a softening point greater than 250℃. CN105567275A discloses a production method for preparing high-purity, high-softening-point asphalt, which uses a combination of stirred-tank oxidation and thin-film evaporator devolatilization to prepare coated asphalt with a softening point of 250-300℃ under a vacuum negative pressure of 0.02 MPa. Patent CN103897714B discloses a method for preparing high-softening-point asphalt for coating natural graphite anode materials for lithium-ion batteries. This invention uses asphalt as raw material and employs a three-stage oxidation process under vacuum negative pressure conditions of 0.06-0.85 MPa to achieve continuous preparation of coated asphalt at 260-290℃. It is evident that current asphalt preparation processes mainly utilize cross-linking or condensation reactions under vacuum pressure, resulting in the removal of a large amount of light components during the reaction. While this ensures a high coking value for the product, the product yield is significantly reduced to only 20-30%, and 70-80% of the raw material is discharged as liquid oil, leading to extremely low raw material utilization. Summary of the Invention

[0004] The present invention aims to provide a process and apparatus for the co-production of petroleum-based impregnated bitumen and coated bitumen, thereby improving the product yield of petroleum-based raw materials.

[0005] To solve the above technical problems, the specific solution adopted in this invention is as follows: a process for the co-production of petroleum-based impregnated asphalt and coated asphalt, wherein petroleum-based raw materials are fractionated to obtain light components and heavy components; the heavy components are subjected to high-gravity devolatilization to obtain impregnated asphalt products and impregnated asphalt with removed light components; the mixture of the light components and the impregnated asphalt with removed light components is mixed with the coated asphalt product and subjected to a high-gravity oxidative crosslinking reaction, wherein the first part of the oxidized asphalt produced by the reaction is continuously recycled into the mixture, and the second part is subjected to high-gravity devolatilization to obtain the coated asphalt product.

[0006] Preferably, it includes the following steps:

[0007] 1) Heat the petroleum-based feedstock to the reaction temperature in a furnace;

[0008] 2) The petroleum-based feedstock from step 1) is cut into light and heavy components by a flash distillation tower;

[0009] 3) The heavy components of the raw material from step 2) are passed through the first supergravity devolatilizer to obtain impregnated bitumen product and impregnated bitumen with light components removed;

[0010] 4) The light component of the raw material from step 2) and the light component of the impregnated asphalt from step 3) are fed into a high-temperature mixing tank, mixed with the coated asphalt product in the high-temperature mixing tank, and then subjected to an oxidative cross-linking reaction through a high-gravity reactor to produce a coated asphalt crude product.

[0011] 5) The first part of the crude oxidized asphalt product from step 4) is recycled back to the high-temperature mixing tank, and the other part is continuously discharged into the second supergravity devolatilization device. The devolatilization treatment in the second supergravity devolatilization device is used to obtain the coated asphalt product.

[0012] Preferably, in step 1), the petroleum-based raw material is heated to 350-400°C.

[0013] Preferably, the fractionation temperature in step 2) is 350-380℃.

[0014] Preferably, in step 3), the rotational speed of the rotating body in the first supergravity devourer is 100-2000 r / min, and the vacuum degree is 0.01-0.1 MPa.

[0015] Preferably, in step 3), the rotational speed of the rotating body in the first supergravity devourer is 1000-2000 r / min, and the vacuum degree is 0.05-0.09 MPa.

[0016] Preferably, in step 4), the rotational speed of the rotating body in the hypergravity reactor is 500-1500 r / min, and the air flow rate is 0.2-0.5 m³ / min. 3 ·kg -1 The reaction pressure is 1.0-4.5 MPa.

[0017] Preferably, in step 4), the rotational speed of the rotating body in the hypergravity reactor is 600-1200 r / min, and the reaction pressure is 1.0-3 MPa.

[0018] Preferably, the coated asphalt product in step 4) is of the same type as the coated asphalt product prepared in step 5).

[0019] Preferably, the mass ratio of the first part and the second part in step 5) is 1-20.

[0020] Preferably, in step 5), the rotational speed of the rotating body in the second hypergravity devourer is 600-2000 r / min, and the vacuum degree is 0.01-0.1 MPa.

[0021] Preferably, in step 5), the rotational speed of the rotating body in the second hypergravity devourer is 800-1800 r / min, and the vacuum degree is 0.08-0.095 MPa.

[0022] Preferably, the petroleum-based feedstock is one or a combination of ethylene tar, catalytic slurry oil, and atmospheric and vacuum residue.

[0023] A petroleum-based impregnated bitumen and coated bitumen co-production device includes a heating furnace, a flash tower, a first ultragravity devolatilizer, a high-temperature stirred tank, an ultragravity reactor, and a second ultragravity devolatilizer connected in sequence; wherein the raw material heavy component outlet of the flash tower is connected to the first ultragravity devolatilizer, the raw material light component outlet is connected to the high-temperature stirred tank, and a circulation reflux pipeline for the crude oxidized bitumen product is provided between the ultragravity reactor and the high-temperature stirred tank.

[0024] This invention proposes a process and apparatus for the co-production of petroleum-based impregnated bitumen and coated bitumen, overcoming the problems of low production capacity and unstable product performance caused by the intermittent operation of current impregnated bitumen and coated bitumen production, especially the low product yield caused by raw material pretreatment and vacuum reaction conditions. By performing a simple flash evaporation treatment on petroleum-based raw materials to separate light and heavy components, the heavy components are processed into impregnated bitumen for ultra-high power graphite electrodes using a high-gravity devolatilization process, while the light components are processed into coated bitumen for lithium-ion battery anodes using a combination of high-gravity oxidation crosslinking and high-gravity devolatilization. This significantly improves product yield and achieves multi-level effective utilization of each component of the raw materials, greatly increasing added value. The impregnated bitumen meets the following specifications: softening point 80-120℃, quinoline insolubles <0.5%, toluene insolubles >10%, and coking value >47%; the coated bitumen meets the following specifications: softening point 180-280℃, quinoline insolubles <1%, and coking value 55-75%.

[0025] Compared with existing technologies, this invention effectively utilizes existing inexpensive petroleum-based by-products in stages to prepare impregnated pitch for ultra-high power graphite electrodes and coated pitch for lithium battery anodes. This not only achieves continuous operation but also significantly increases product yield, thereby maximizing product benefits. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of a process and apparatus for the co-production of petroleum-based impregnated bitumen and coated bitumen according to the present invention;

[0027] Figure 2 This is a diagram showing the specific properties of the petroleum-based raw materials used in various embodiments of a petroleum-based impregnated bitumen and coated bitumen co-production process of the present invention.

[0028] Figure 3 The diagram shows the property data of impregnated bitumen and coated bitumen products prepared in various embodiments of the co-production process of petroleum-based impregnated bitumen and coated bitumen of the present invention.

[0029] The diagram is labeled as follows: 1. Heating furnace, 2. Flash tower, 3. First high-gravity devolatilizer, 4. High-temperature stirred tank, 5. High-gravity reactor, 6. Second high-gravity devolatilizer, 7. Petroleum-based feedstock, 8. High-temperature petroleum-based feedstock, 9. Heavy components of feedstock, 10. Light components of feedstock, 11. Removal of light components from impregnated bitumen, 12. Impregnated bitumen product, 13. Mixture, 14. Oxidized bitumen crude product for recycling, 15. Air, 16. Generated oil and gas, 17. Oxidized bitumen crude product, 18. Coated bitumen product, 19. Volatile matter. Detailed Implementation

[0030] like Figure 1As shown, a petroleum-based impregnated bitumen and coated bitumen co-production device of the present invention includes a heating furnace 1, a flash tower 2, a first hypergravity devolatilizer 3, a high-temperature stirred tank 4, a hypergravity reactor 5, and a second hypergravity devolatilizer 6. The inlet of the flash tower 2 is connected to the heating furnace 1, the bottom outlet of the flash tower 2 is connected to the first hypergravity devolatilizer 3, and the top gas phase outlet is connected to the gas phase outlet of the hypergravity devolatilizer and the inlet of the high-temperature stirred tank 4. The inlet of the hypergravity reactor 5 is connected to the outlet of the high-temperature stirred tank 4, and the liquid material outlet of the hypergravity reactor 5 is connected to the upper part of the high-temperature stirred tank 4 and the second hypergravity devolatilizer 6 through a three-way valve and a control valve, respectively.

[0031] Based on the above co-production equipment, a process for co-producing petroleum-based impregnated bitumen and coated bitumen according to the present invention includes the following steps:

[0032] 1) Petroleum-based raw materials are heated to 350-400℃ in a heating furnace and continuously fed at a certain flow rate.

[0033] 2) The high-temperature petroleum-based feedstock from step 1) is cut into light components with an initial boiling point of ~350℃ or ~380℃ and heavy components with a boiling point greater than 350℃ or greater than 380℃ by flash distillation tower 2.

[0034] 3) The heavy components of the raw material from step 2) enter from the side of the first supergravity devolatilizer 3 to begin the process of removing the light components from the crude impregnated asphalt product. The rotation speed of the rotating body in the supergravity devolatilizer is 100-2000 r / min, and the vacuum degree of the device is 0.01-0.1 MPa. Preferably, the rotation speed of the rotating body in the first supergravity devolatilizer 3 is 1000-2000 r / min, and the vacuum degree is 0.05-0.09 MPa. The removed light components are discharged from the top, and the impregnated asphalt product is discharged from the bottom.

[0035] 4) The light components of the raw material from step 2) and the light components of the impregnated asphalt from step 3) are fed together into a high-temperature stirred tank 4. After mixing with the coated asphalt product (with the same model as the final coated asphalt product) in the tank, they enter a high-gravity reactor 5. Crosslinking air enters from one side, initiating the oxidative crosslinking reaction and producing crude oxidized asphalt. The rotational speed of the rotating body in the high-gravity reactor 5 is 500-1500 r / min, the air flow rate is 0.2-0.5 m³·kg⁻¹ (the ratio of air flow rate m³·h⁻¹ to petroleum-based raw material flow rate kg·h⁻¹), and the reaction pressure is 1.0-4.5 MPa. The preferred rotational speed of the high-gravity reactor 5 is 600-1200 r / min, and the reaction pressure is 1-3 MPa. Because the high-gravity reactor 5 can enhance gas-liquid contact, it can significantly shorten the oxidative crosslinking reaction time, and the crosslinking depth can be improved through intermediate product recycling, producing oxidized asphalt with suitable softening point and coking value, which is then fed into subsequent processes.

[0036] 5) A portion (labeled m1) of the crude oxidized asphalt product from step 4) is continuously circulated back to the high-temperature stirred tank 4 at a certain mass ratio. The other portion, as crude product (labeled m2), is continuously discharged and enters the second hypergravity devolatilizer 6, where the circulation ratio (m1 / m2) is 1-20. The crude oxidized asphalt product enters from the side of the second hypergravity devolatilizer 6 to begin the removal of light components from the oxidized asphalt. The rotational speed of the rotating body in the second hypergravity devolatilizer 6 is 600-2000 r / min, and the vacuum degree of the device is 0.01-0.1 MPa. The removed light components are discharged from the side, while the coated asphalt product is discharged from the bottom. The preferred rotational speed of the second hypergravity devolatilizer 6 is 800-1800 r / min, and the vacuum degree is 0.08-0.095 MPa. The hypergravity devolatilizer utilizes rotation to generate a simulated, controllable hypergravity (centrifugal force field) environment for the transfer and mass transfer process. In a hypergravity environment, molecular diffusion and interphase mass transfer between molecules of different sizes are much faster than in a normal gravity field. Gas-liquid, liquid-liquid, and liquid-solid two-phase flows and contacts in porous media (packing) under hypergravity conditions hundreds to thousands of times greater than Earth's gravity. The enormous shear force breaks the liquid into nanoscale films, filaments, and droplets, creating huge and rapidly renewing phase interfaces. This significantly shortens the diffusion distance between different phases, increasing the interphase mass transfer rate by 1-3 orders of magnitude compared to traditional towers, thus greatly enhancing the interphase mass transfer process. By using centrifugal force to transport oxidized asphalt in the chamber to the rotating packing, the gas-liquid mass transfer process is enhanced by the relatively flowing desorbed gas, achieving polymer devolatilization.

[0037] The continuous production in this invention refers to the continuous input of raw materials into the heating furnace 1, flash tower 2, high-temperature stirred tank 4, first hypergravity devolatilizer 3, hypergravity reactor 5, and second hypergravity devolatilizer 6, with continuous output of coated asphalt and impregnated asphalt products. Currently, commercial technologies all employ intermittent operation with long-duration single-reactor reactions. However, because the hypergravity reactor enhances gas-liquid contact, the oxidative crosslinking reaction time can be significantly shortened, and the crosslinking depth can be increased through intermediate product recycling, producing oxidized asphalt with suitable softening point and coking value for subsequent processing stages.

[0038] This process features a short distillation range and eliminates the need for raw material sedimentation and heating purification. It directly oxidizes and cross-links petroleum-based feedstocks, combined with subsequent removal of light components, to produce impregnated bitumen for ultra-high-power graphite electrodes and coated bitumen for lithium-ion anodes. The oxidative cross-linking reaction not only enables the interconnection of molecules in the raw materials to form large molecular groups, rapidly increasing the softening point and significantly reducing reaction time, thereby lowering energy consumption, but also allows small molecules of light components to cross-link into large molecules through oxygen atoms, improving the utilization rate of small molecules and thus increasing product yield.

[0039] The following uses ethylene tar from a Sinopec refinery as the petroleum-based feedstock (the specific properties of ethylene tar are as follows). Figure 2 As shown in the figure, the continuous production process of petroleum-based coated bitumen of the present invention is illustrated through four embodiments. In other embodiments of the present invention, the petroleum-based feedstock is one or more of ethylene tar, catalytic slurry oil, and atmospheric and vacuum residue.

[0040] Example 1

[0041] Ethylene tar is heated to 350°C in heater 1 and then enters flash tower 2, where it is separated into light components with an initial boiling point of ~350°C and heavy components with a boiling point above 350°C. The heavy components then enter the first high-gravity devourer 3, where the rotating body rotates at 1000 r / min and the vacuum is 0.04 MPa. The light components are mixed with the light components removed from the impregnated bitumen in the first high-gravity devourer 3 and then enter a high-temperature stirred tank 4, which then enters a high-gravity reactor 5 for oxidative crosslinking reaction. The reaction pressure in the high-gravity reactor 5 is 1 MPa, the rotating body rotates at 600 r / min, and the air volume is 0.25 m³·kg⁻¹. -1 The circulation ratio of the crude oxidized asphalt product is 7, the rotation speed of the rotating body in the second supergravity devourer 6 is 800 r / min, and the vacuum degree is 0.08 MPa.

[0042] Example 2

[0043] Same as Example 1, except that the rotational speed of the rotating body in the first hypergravity devourer 3 is 1500 r / min and the vacuum degree is 0.06 MPa; the air flow rate into the hypergravity reactor 5 is 0.35 m³·kg. -10

[0044] Example 3

[0045] Ethylene tar is heated to 380°C in heater 1 and enters flash tower 2, where it is broken down into light components with an initial boiling point of ~380°C and heavy components with a boiling point above 380°C. The heavy components enter the first high-gravity devourer 3, where the rotating body rotates at 1500 r / min and the vacuum is 0.08 MPa. The light components are mixed with the light components removed from the impregnated bitumen in the first high-gravity devourer 3 and enter the high-temperature stirred tank 4, which then enters the high-gravity reactor 5 for oxidative crosslinking reaction. The reaction pressure in the high-gravity reactor 5 is 2 MPa, the rotating body rotates at 1000 r / min, the air volume is 0.3 m3·kg-1, and the recycling ratio of the crude oxidized bitumen product is 15. The rotating body in the second high-gravity devourer 6 rotates at 1200 r / min and the vacuum is 0.08 MPa.

[0046] Example 4

[0047] Same as Example 3, except that in the first hypergravity devolatilizer 3, the rotational speed is 2000 r / min and the vacuum degree is 0.09 MPa; the reaction pressure in the hypergravity reactor 5 is 4 MPa, the rotational speed is 1000 r / min, and the air volume is 0.4 m³·kg. -1 The circulation ratio of oxidized asphalt is 20, the rotation speed of the rotating body in the second supergravity devourer 6 is 1800 r / min, and the vacuum degree is 0.095 MPa.

[0048] like Figure 3 As shown, the softening point of the coated asphalt product prepared by the process of this invention is 140-300℃, the quinoline insoluble matter is <1%, and the coking value is 46-80%; the softening point of the impregnated asphalt product is 80-120℃, the quinoline insoluble matter is <0.5%, the toluene insoluble matter is >10%, and the coking value is >47%. Thus, while ensuring the various indicators of the product, continuous production of the equipment is achieved, and the yield reaches more than 60%, which greatly improves the raw material benefits.

Claims

1. A process for the co-production of petroleum-based impregnated bitumen and coated bitumen, characterized in that: The process involves fractionating a petroleum-based feedstock to obtain light and heavy components; subjecting the heavy components to high-gravity devolatilization to obtain an impregnated bitumen product and a low-gravity impregnated bitumen product; mixing the light components and the low-gravity impregnated bitumen product with the coated bitumen product and then subjecting the mixture to a high-gravity oxidative crosslinking reaction. The first portion of the oxidized bitumen produced is continuously recycled into the mixture, and the second portion is subjected to high-gravity devolatilization to obtain the coated bitumen product. The process includes the following steps: 1) Heat the petroleum-based feedstock to the reaction temperature in a furnace; 2) The petroleum-based feedstock from step 1) is processed into light and heavy components using a flash distillation tower; 3) The heavy components of the raw material from step 2) are passed through the first supergravity devolatilizer to obtain impregnated bitumen product and impregnated bitumen with light components removed; 4) The light component of the raw material from step 2) and the light component of the impregnated asphalt from step 3) are fed into a high-temperature mixing tank, mixed with the coated asphalt product in the high-temperature mixing tank, and then subjected to an oxidative cross-linking reaction through a high-gravity reactor to produce a coated asphalt crude product. The first part of the coated asphalt crude product from step 4) is recycled back to the high-temperature mixing tank, and the other part is continuously discharged into the second ultragravity devolatilization device. The coated asphalt product is obtained by devolatilization treatment in the second ultragravity devolatilization device. In step 1), the petroleum-based feedstock is heated to 350-400℃; in step 2), the fractionation temperature is 350-380℃; in step 3), the rotational speed of the rotating body in the first hypergravity devourer is 100-2000 r / min, and the vacuum degree is 0.01-0.1 MPa; in step 4), the rotational speed of the rotating body in the hypergravity reactor is 500-1500 r / min, and the air flow rate is... The reaction pressure is 1.0-4.5 MPa; the coated asphalt product in the high-temperature stirred tank in step 4) is the same model as the coated asphalt product prepared in step 5); the mass ratio of the first part and the second part in step 5) is 1-20; the rotation speed of the rotating body in the second supergravity devourer in step 5) is 600-2000 r / min, and the vacuum degree is 0.01-0.1 MPa.

2. The process for co-producing petroleum-based impregnated bitumen and coated bitumen as described in claim 1, characterized in that: The petroleum-based feedstock is one or more of the following: ethylene tar, catalytic slurry oil, and atmospheric and vacuum residue.

3. The process for co-producing petroleum-based impregnated bitumen and coated bitumen as described in claim 1, characterized in that: The process is implemented using a co-production unit, which includes a heating furnace, a flash tower, a first ultragravity devolatilization unit, a high-temperature stirred tank, an ultragravity reactor, and a second ultragravity devolatilization unit connected in sequence. The heavy component outlet of the flash tower is connected to the first ultragravity devolatilization unit, and the light component outlet is connected to the high-temperature stirred tank. A circulation reflux pipeline for the crude oxidized asphalt product is also provided between the ultragravity reactor and the high-temperature stirred tank.

Citation Information

Patent Citations

  • A method for preparing high softening point pitch for coating natural graphite anode materials for lithium-ion batteries

    CN103897714B

  • Preparation method for high-purity high-softening-point asphalt

    CN105567275A

  • Continuous production method for asphalt base carbon material

    CN107163971A

  • Continuous production method of lithium ion battery negative electrode coating material

    CN112592734A

  • Treatment device and treatment method for coking wastewater

    CN107879461A